L’ouvrage à cornes de Saint-Jean à Soissons : vestiges archéologiques et essai de contexte historique - Vincent Buccio (Archéologie Médiévale, 2019)
The partial excavation of an outwards project in fortified urban building in Soissons (Aisne), built and dismantled in the course of the 19th century, gave us the opportunity to compare the abundant archival records related to this building and field observations. Archaeology allows us to verify the reliability of written sources and shed light on parts of the history of the fortification that are not informed by the texts. Therefore, this study allows us to follow the evolution of a building from its early sketches to its dismantling, as well as its construction or the functioning hazards met along the way. At the end of this study, it is possible to measure the relevance of the excavation of a recent structure, despite the great number of preserved archived documents.